Efficacy of silver nanoparticles (NPs) and fungal elicitors on the curcuminoid production in Curcuma longa L - Praveen, Aishwarya (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.